Práticas educomunicativas no contexto escolar: obstáculos e perspectivas - Hoppe, Barbara Chiodini Axt (2016)
This research aims to address on the pioneering educational experiment carried out in the Community of Cerro Pelado in Uruguay, with the radio El Chasque FM, started as communication design and currently as a curricular discipline of a small rural school, which seeks in their practices encourage reflection and a real social intervention, leaving a space open to the outcrop of the feelings, thoughts, ideas and different understandings of the persons involved, about themselves, about others and about the world around them, is investigating and discussing these dynamics on the interrelationships of the various types of knowledge that arise from the integration of the areas of education and communication, educational communication. This has been shown viable tool in creating new types of learning, formal or informal, with bias more democratic, egalitarian and less hierarchical, given the plurality and cultural diversity, becoming emerging and necessary practice to be propagated, raising up possible in this process of reconstruction looks on the training of our future professionals of education-communication, the educommunicators. Therefore, we performed a case study that led to the investigation of educomunicativas practices and their possible effects and consequences that the school context.